The good doctor. Season three [videorecording (DVD)] - Shore, David, 1960- (Sony Pictures Home Entertainment, 2020)
The show is about a young surgeon with autism who is recruited to work at a pediatric unit of a hospital. The hospital is known for treating many of the toughest cases a surgeon could ever see, but with autism comes clarity that most surgeons will never have. The television series focuses on the relationship between the doctor and patient, and how a man who cannot relate to the people who he tries to help.